Spatial autocorrelation of dengue in relation to population density in Balangan District, Indonesia: an ecological study - Ridha, Muhammad Rasyid; Yudhastuti, Ririh; Ambar Garjito, Triwibowo; Norjanah, Norjanah; Juhairiyah, Juhairiyah; Andiarsa, Dicky; Norleyandi, Untung (Intelektual Pustaka Media Utama, 2024)
Dengue in Balangan Regency has the 2nd highest incidence rate (IR) in South Kalimantan at 126.64 per 100,000 population. This study aimed to determine the distribution pattern and conduct spatial analysis of dengue with population density in Balangan Regency. This quantitative research requires secondary data of dengue cases and Population Density in time series 2017-2021 with spatial analysis methods. The results showed that high dengue cases were in areas that had high density. Based on spatial analysis, dengue cases have a positive spatial relationship in 2017-2019 and a negative spatial relationship in 2020-2021 where dengue cases have a non-clustered distribution pattern (spread). Paringin City, East Paringin, Bungin, Maradap, Panggung, and Awayan villages are categorized as high-highly vulnerable to dengue. The findings of this study indicate that there is an influence of population density on the incidence of dengue. Monitoring of areas with high population density using spatial analysis is necessary for early detection of areas with high potential for dengue incidence.